Synthesis of silver nanoparticles in chitosan, gelatin and chitosan/gelatin bionanocomposites by a chemical reducing agent and their characterization - Ahmad @ Ayob, Mansor; Lim, Jenn Jye; Shameli, Kamyar; Ibrahim, Nor Azowa; Tay, Mei Yen (MDPI, 2011)
In this research, silver nanoparticles (AgNPs) were synthesized in chitosan (Cts), Cts/gelatin and gelatin suspensions using a chemical reducing agent. Cts and gelatin were used as natural stabilizers and solid support, whereas AgNO3 was used as the silver precursor. Sodium borohydride (NaBH4) was used as the reducing agent. The properties of AgNPs in Cts, Cts/gelatin and gelatin bionanocomposites (BNCs) were studied in terms of their surface plasmon resonance, crystalline structure, average diameter size, particle distributions, surface topography and functional groups. All the samples were characterized by UV-visible spectroscopy, powder X-ray diffraction, transmission electron microscopy, atomic force microscopy and Fourier transform infrared spectroscopy.